Effectiveness comparison of guided discovery and semi-guided discovery learning models toward the fact-finding skill on plantae material - Galuh Arga Wisnu Saputra; Bambang Subali (Universitas Ahmad Dahlan, 2019)
The purpose of this research was to discover the differences in learning outcomes of fact-finding in the implementation of guided discovery and semi-guided discovery learning models on plantae material at X grade of National 1 High School of Jetis Bantul. This research was conducted on experimental group class that carried out learning with guided discovery and the control class with semi-guided discovery learning. The design of this research was the randomized pretest-posttest control group design. The quantitative data were the learning outcomes of cognitive domain which obtained from the values of pretest and posttest, that analyzed through T test at 5% significance level. Based on the test, it was obtained p=0.000 (p<0.05) so there was a significant difference between the guided discovery and semi-guided discovery learning model toward the fact-finding skill on the learning outcomes of student. The fact-finding skills of guided discovery was higher than semi-guided discovery learning with pretest average of control class students (41.53) and the experimental class (41.97), while the postest average of control class (69.75) and experimental class (80.66). The learning through the implementation of guided discovery learning model was more effective than semi-guided discovery learning model toward fact-finding skill.